Design and implementation of a 2.4 GHz energy harvester - Gan, Felix Si Zhou (Nanyang Technological University, 2020)
This paper details the basic concepts and processes of RF energy harvesting needed to design and implement a 2.4GHz energy harvester. RF energy as a renewable source of energy and its applications are explored and its variables determined. The Siretta Delta 7A Wi-Fi antenna was chosen as the RF receiver for this project and the Advanced Design System (ADS) software was utilised to simulate the performance of the circuit components and design. The component parameters and most efficient circuit design were also determined using transient simulation and harmonic balance simulation respectively. The Karthaus-Fischer cascade voltage multiplier design was selected to be integrated with an impedance matching circuit to maximise conversion efficiency and reduce losses. The parameters of the impedance matching circuit were determined using the smith chart utility tool in ADS. The Altium Designer software was used for PCB design, enabling the hardware to be fabricated. The harvester will then be tested and its voltage output and efficiency will be compared to the ideal values obtained from the simulation. Further research and recommendations would be explored to improve the overall circuit efficiency and viability.